Application of Fuzzy Analytic Hierarchy Process (FAHP) in choosing a comprehensive university for medical course / Nurul Suhada Aziz …[et al.] - Aziz, Nurul Suhada; Hamzah, Muhammad Umirul Amir; Md Zaherruddin, Nur Qistina; Abdullah, Siti Zulaikha (Universiti Teknologi MARA, Kelantan, 2023)
The Malaysian education system offers a wide range of courses to school leavers in public and private universities. Medical course is one of the courses chosen by outstanding students. Several universities across the country offer such courses. This study is going to determine the most favorable comprehensive universities in Malaysia that offer medical courses and examine the ranking of criteria that have an impact on choosing universities. Specifically, this study applied fuzzy triangular numbers (TFN) and fuzzy analytic hierarchy process (FAHP) to multi-criteria decision-making (MCDM). A set of questionnaires was distributed to the students of matriculation session 2020/2021 which were from Module I. Responses were analyzed using Microsoft Excel based on FAHP Chang's model. FAHP shows the first rank university having the highest total weight vector. Universiti Malaysia Sabah (UMS) get the first rank based on the criteria chosen.